Flying High with Strategic HR: Transforming Business Operations in the Aviation Sector - Miko Andi Wardana; Dede Ardian; Fajar Islam (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research investigates the impact of strategic human resources practices and operational efficiency on business performance within the aviation sector, with a focus on Employee Engagement and Organizational Culture as mediating factors. The study utilized a quantitative approach with a sample of 82 staff members from Juanda International Airport, applying a random sampling technique and employing SmartPLS for data analysis. The research examined how Recruitment and Selection and Training and Development influence Employee Engagement, which in turn affects Business Performance. It also explored how Process Optimization and Resource Management impact Operational Efficiency and, subsequently, Business Performance. The findings indicate that both Recruitment and Selection and Training and Development significantly enhance Employee Engagement, which positively influences Business Performance. Operational Efficiency, influenced by Resource Management, also affects Business Performance, though Process Optimization did not show a direct significant effect. Organizational Culture emerged as a critical mediator, linking Operational Efficiency to Business Performance. The study underscores the importance of integrated strategic human resources practices and efficient operational processes in optimizing business outcomes. These results provide valuable insights for organizations aiming to improve their performance through effective human resources and operational strategies. Future research is suggested to explore additional variables and contexts to deepen the understanding of these relationships.